A Study on Facial Expression and First Impression Through Machine Learning - Lee, Won Chan; Yoon, Daekyun (1st International Conference on Artificial Intelligence in Information and Communication, ICAIIC 2019, 2019)
The first impression is very important in human relationships. It forms in a short time and lasts long. The influence of the first impression is so great that many people want to have a good first impression. Unfortunately, the specific way to make a good first impression was not revealed. Instead, there are many abstract ways like make a smile. However, it is not clear what kind of smile is fit. Because there are so many kinds of smile. So, it's not a specific way for anyone. In this research, we are going to analyze facial expressions and first impression with numerical data by utilizing machine learning. After finding the feature that determines the good first impression and proposes a specific way to make a good first impression.
Keywords: Facial Expressions; First impressions; Human relationships; Numerical data; Face Detection; Facial Expression; First Impression; Machine Learning